Introduction to Real Analysis - Bartle, Robert G.; Sherbert. Donald R (New Delhi: Wiley, 2011)
Introduction to Real Analysis is a comprehensive book for undergraduate students of Mathematics. The book comprises chapters on preliminaries, the real numbers, sequences and states, limits, continuous functions, differentiation, infinite series, and the generalized Reimann Integral. In addition, the book consists of several chapterwise problems to understand the concepts better. This book is essential for students who aspire to learn the basic concepts and techniques of real analysis.
Appendix A-E 348-370p.; References 371p.; Index 395-402p.; Reprint 2015.
Keywords: Differentation; Infinite series; Limits